Pengaruh Workshop Media Pembelajaran Terhadap Peningkatan Kompeteni Guru Dalam Mengembangkan Media Pembelajaran - Muh. Afandy Gunawan Lahami (JOURNAL OF EDUCATIONAL TECHNOLOGY, CURRICULUM, LEARNING AND COMMUNICATION, 2021)
The purpose of this research is to describe the implementation of instructional media workshops, describe the competence of teachers in developing presentation media, and find out whether there is an effect of instructional media workshops on increasing teacher competence in developing learning media at SMP Negeri 18 Makassar. The approach used is descriptive qualitative research, while the type of research used in this research is descriptive qualitative, referring to the correlation study (relationship). The data analysis used descriptive analysis and inferential statistical analysis. The results of this study indicate that the implementation of the instructional media workshop shows very effective results based on the observations of the instructor and training participants. The pretest and posttest results showed that there were significant differences. This also answers the hypothesis H1 = There is an Effect of Learning Media Workshop on Increasing Teacher Competence in Developing Learning Media at SMP Negeri 18 Makassar. Keywords: Education and training, Teacher, Learning Media,Teacher Competence